The Occurrence and Genomic Characteristics of mcr-1-Harboring Salmonella from Retail Meats and Eggs in Qingdao, China - Changan Li; Xiulei Gu; Liping Zhang; Yuqing Liu; Yan Li; Ming Zou; Baotao Liu (Foods, 2022)
Salmonella are widely distributed foodborne pathogens and are often associated with food animal products. Colistin resistance mediated by mcr-1 is an increasing threat; however, data on the characteristics of mcr-1-harboring Salmonella among retail foods are still lacking. In this study, retail meats from 24 supermarkets and eggs from nine markets in Qingdao city were investigated to determine the presence and genomic characteristics of mcr-1-harboring Salmonella. We found the retail meats and eggs were highly contaminated by Salmonella, with detection rates of 17.5% (31/177) and 12.3% (16/130), respectively. A total of 76 Salmonella isolates were obtained in this study, and 77.6% showed multidrug resistance (MDR). The MDR proportion of egg isolates (97.5%) was significantly higher than that in meat isolates (55.6%) (p < 0.05). The most prevalent Salmonella serotypes were Typhimurium (56.6%) and Enteritidis (17.1%). Of the 76 Salmonella isolates, 40 possessed mcr-1. All 40 mcr-1-positive isolates were ST34 S. Typhimurium and were from eggs of eight brands. Different mcr-1-harboring isolates existed in the same egg, and some isolates from different egg samples or brands showed clonal relationships. The mcr-1 was located on similar IncHI2/HI2A MDR non-conjugative plasmids lacking transfer region, resulting in the failure of conjugation. The phylogenetic tree using genome sequences showed that the mcr-1-positive isolates from eggs clustered together with mcr-1-positive isolates from chicken and humans in China, revealing that mcr-1-positive egg-borne Salmonella might be derived from chicken and could potentially trigger outbreaks in humans. The high occurrence of mcr-1-harboring Salmonella in fresh eggs is alarming, and there is an urgent need to monitor mcr-1-harboring Salmonella in retail meats and eggs. We report for the first time the role of retail eggs in disseminating mcr-1-positive Salmonella and the risk of transmission of these MDR pathogens from retail food to humans should be evaluated comprehensively.